Ozone loss derived from balloon-borne tracer measurements and the SLIMCAT CTM - Robinson, A. D.; Millard, G. A.; Danis, F.; Guirlet, M.; Harris, N. R. P.; Lee, A. M.; Mcintyre, J. D.; Pyle, J. A.; Arvelius, J.; Dagnesjo, S.; Kirkwood, S.; Nilsson, Hans; et al. (HAL CCSD, 2004)
International audience Balloon-borne measurements of CFC-11 (on flights of the DIRAC in situ gas chromatograph and the DESCARTES grab sampler), ClO and O 3 were made during the 1999/2000 winter as part of the SOLVE-THESEO 2000 campaign. Here we present the CFC-11 data from nine flights and compare them first with data from other instruments which flew during the campaign and then with the vertical distributions calculated by the SLIMCAT 3-D CTM. We calculate ozone loss inside the Arctic vortex between late January and early March using the relation between CFC-11 and O 3 measured on the flights, the peak ozone loss (1200 ppbv) occurs in the 440–470 K region in early March in reasonable agreement with other published empirical estimates. There is also a good agreement between ozone losses derived from three independent balloon tracer data sets used here. The magnitude and vertical distribution of the loss derived from the measurements is in good agreement with the loss calculated from SLIMCAT over Kiruna for the same days.